AUTOMATION OF SMALL HYDRO POWER PLANTS AS MEAN OF INCREASE THE EFFICIENCY OF THEIR OPERATION IN ELECTRICAL NETWORK - Lezhnyuk, Petro; Ngoma, Jean-Piere; Kilimchuk, Anton (Scientific Works of Vinnytsia National Technical University, 2015)
The principles of creation of automated control system for small HPP are considered. It is shown, that such system should be hierarchical, formed at basic HPP and rely on lower level on local automatic systems.